Can Peritoneal Dialysis Be The First-Line Treatment For End-Stage Kidney Disease? A SWOt Analysis - Sasmitaningsih, Irine Puspita; Aviati, Kurnia; Lukitasari, Putri Emyta; Mahananny, Nonnytha; Pranasari, Maria Carisita Suci Puspa; Sukartini, Ni Made (Yayasan Jompa Research and Development, 2025)
End-stage kidney disease (ESKD) is a global health challenge, with kidney transplantation being the preferred treatment. However, due to a shortage of donor organs and medical complications, many patients rely on dialysis. Peritoneal dialysis (PD) is a promising alternative but is underused compared to hemodialysis (HD). This study explores whether PD could be considered a first-line treatment for ESKD, using a SWOT analysis to assess its strengths, weaknesses, opportunities, and threats. Method Systematic literature review (2015–2025) with SWOT framework. PD improves patients' quality of life with treatment flexibility and better preservation of kidney function. However, the risk of infection such as peritonitis is a weakness in the widespread use of PD therapy in the elderly and remote areas. The development of PD use requires government support in equalizing the distribution of healthcare professionals skilled in PD and providing reasonable cost reimbursement. PD has the potential to be an effective first-line treatment for ESKD, but its widespread use is constrained by various challenges. Addressing these barriers could enhance its accessibility and efficacy.